• Support PF! Buy your school textbooks, materials and every day products Here!

Need help proving solution of a differential equation

  • Thread starter furth721
  • Start date
  • #1
6
0
I need help proving the general soultion to this equation, dy/dx=(y-(y^2))/x, is x/(x+C)

where C cannot equal -x. When I separate the variables and integrate I get

ln|y|-ln|1-y|=ln|x|+C, and I cannot make this look like the general solution. I'm not sure if

I did the integration wrong but I think it is right. Im not too sure what to do after I

integrate. Any help would be greatly appreciated. Thanks
 

Answers and Replies

  • #2
699
5
Your integration is correct. Try combining the ln y functions and then raising both sides to the e power. From there, it should just be a simplification problem to solve.
 
  • #3
699
5
Once you simplify, you may not see it right away I noticed when doing the simplification myself.

You should end up with y=-xc/(1-xc) but if we multiply the top and the bottom by (-1/c)/(-1/c), we would get x/[(-1/c)+x]. -1/c=c2 or C depending on how you want to notate it. Thus, yielding x/(C+x)
 
  • #4
6
0
Im not sure how you ended up with y=-xc/(1-xc) when I combine the ln functions and raise to the e power I get y/(1-y)=x+C then you can change that into (1-y)/y=1/(x+C), then (1/y)-1=(1/x+C) im not sure if that is the way you did it so can you please elaborate more on how you got y=-xc/(1-xc). Sorry if I am being difficult i usually dont have this much trouble with these kind of problems. thanks
 
Last edited:
  • #5
699
5
First of all, elnx + c= Cx not x+c.

That means you will have y/(1-y)=Cx

Next, you need to multiple both sides by (1-y); thus, obtaining y=Cx(1-y)=Cx-ycx.

Now just add yCx to both sides. y+yCx=Cx.

Then factor: y(1+Cx)=Cx.

y=Cx/(1+Cx)

Multiple by (1/c)/(1/c) which is equal to 1.

y=x/((1/c)+x) and 1/c is just another constant.

y=x/(C2+x)
 
  • #6
6
0
A HA!!!!!! That makes perfect sense now you have to raise the entire right side of the equation to the e not just ln|x| to the e power plus c to the e power, because you raised ln|y/(1-y)| to the e power, wow, thanks you definitely saved me from a lot of frustration
 
Last edited:
Top